A new scheme of 2:1 photonic multiplexer and multiplexer-based NOT, OR, AND logic gates in electro-optic Mach–Zehnder interferometer - Sourabh Kumar Das; Nirmalya Pahari (e-Prime: Advances in Electrical Engineering, Electronics and Energy, 2023)
This paper introduces the development of NOT, OR, and AND logic gates utilizing a 2:1 Multiplexer (MUX) based on a titanium-diffused lithium niobate electro-optic Mach–Zehnder interferometer. The shift towards large-scale optical integrated circuits as an alternative to traditional CMOS technology has gained traction, driven by the growing demand for high-speed computation and data transfer rates, reaching up to the terahertz scale, along with the need for energy-efficient interconnects. To optimize the design and reduce the number of photonic MUX, we leverage Shannon decomposition and Reduced Binary Decision Diagram mapping in the creation of MUX-based combinational and logic circuits. The entire design undergoes comprehensive simulation and verification using OPTIBPM with a beam propagation method (BPM). The wafer dimensions for the 2:1 electro-optic MZI-MUX and MUX-based NOT, AND, OR gates are 33 mm × 100 μm, classifying them as integrated optics. The proposed photonic MUX-based combinational circuits exhibit rapid response times, making them particularly advantageous for communication systems, transmission networks, and various industrial applications. Key device parameters, including insertion loss (0.0012 dB), extinction ratio (ER) (28.97 dB), and contrast ratio (29.5 dB), fall within acceptable limits. The BPM simulated results align well with the mathematical computations based on PYTHON simulations.